First record Octopus ‘Octopus’ selene Voss, 1971 (Cephalopoda: Octopoda) in Peruvian waters, with notes of their geographical distribution - Cardoso, Franz (2019)
In this paper, ‘Octopus’ selene is first registered in Peruvian waters and its distribution range extends south to Cabo Blanco, Piura, Peru. Four male specimens of 34 – 50 mm ML were captured between 03°34'S and 04°06'S at depths of 109 – 150 m. A brief description is provided, with taxonomic observations and comments on its geographical distribution of this species.